Papuan Indigenous Family Management to Respond to the Importance of Education in the Challenges of the Globalization Era in Poo Village, Jagebob District, Merauke Regency - Sopia Betaubun; Irene Ipijei; Paskalina Silubun; Simon Rahanau (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to find out the role of Indigenous Papuan Family Management in Responding to the Importance of Education in the Challenges of the Globalization Era in Kampung Poo, Jagebob District, Merauke Regency. This research is a quantitative study with a sampling technique using simple random sampling of 40 people at random. The data collection method was carried out by observation, interviews, documentation, and questionnaires, then after the data was collected, it was followed by data analysis using descriptive statistical analysis with validity and reliability tests using SPSS 22. The results of research on 40 respondents showed that r count > r table. The validity test carried out using SPSS 22 was declared valid for all questions, the results of the reliability test were declared reliable.